Effect of the length of alkyl side chains in the electronic structure of conjugated polymers - Oliveira, Eliezer Fernando [UNESP]; Lavarda, Francisco Carlos [UNESP] (ABM, ABC, ABPol, 2014)
Computational modeling studies of conjugated polymers have been shown to present many challenges. One such challenge is to find ways to reduce the computational cost for these studies without compromising the quality of the results. An approach longly used in the literature for this purpose is replacing long alkyl side chains (with six or more carbons) with a methyl group. This work reports on a theoretical study conducted with the conjugated polymer poly(3-hexylthiophene), which contains a hexyl side chain attached to the monomer, to verify the influence of the size of the alkyl side chain on its electronic structure. The results indicated that, for polymers containing long alkyl side chains, replacement with a propyl group offered full saturation of all properties under review, showing it to be a good approach.
Keywords: computer modeling; conjugated polymers; electronic structure calculation; poly(3-hexylthiophene); P3HT; exciton binding energy